Share pledges and margin call pressure - Chan, Konan; Chen, Hung-Kun; Hu, Shing-yang; Liu, Yu-Jane (Journal of Corporate Finance, 2018)
It is common practice worldwide for corporate insiders to put up stock as collateral for personal loans. We highlight a potential problem in such pledging. When controlling shareholders face a margin call threat if stock prices fall below the required level for a loan, they have an incentive to use corporate resources for their private benefit. We develop and test a margin call hypothesis that controlling shareholders may initiate share repurchases to fend off potential margin calls associated with pledged stocks in order to maintain their control rights. Investors seem to recognize such behavior and discount the potential benefits of repurchase programs. However, share pledges are not reliably related to repurchases when control rights are not a concern. We further show that regulatory restrictions of control rights on pledging effectively reduce the likelihood of firms' repurchasing. Overall, our results shed light on the impact of share pledges on corporate decisions.